1982
DOI: 10.1063/1.331037
|View full text |Cite
|
Sign up to set email alerts
|

Surface flashover of solid dielectric in vacuum

Abstract: The surface of a solid dielectric insulator becomes electrically charged when subjected to a high-voltage stress in vacuum. A method for calculating the surface flashover voltage based on the assumption that the discharge occurs in a layer of desorbed gases from the insulator surface is proposed. The electric field strength required to cause surface flashover is calculated by taking into account the secondary electron emission characteristics of the dielectric material. The dependence of the surface flashover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(73 citation statements)
references
References 8 publications
3
70
0
Order By: Relevance
“…The input of electron avalanches into the dark emission current is also confirmed by estimations based on the model of electron avalanche 22 . The influence of the transverse magnetic field should be visible when the electron gyroradius r c = v e m e c/eB will be comparable with the mean free path of electrons along the surface.…”
Section: Usamentioning
confidence: 51%
“…The input of electron avalanches into the dark emission current is also confirmed by estimations based on the model of electron avalanche 22 . The influence of the transverse magnetic field should be visible when the electron gyroradius r c = v e m e c/eB will be comparable with the mean free path of electrons along the surface.…”
Section: Usamentioning
confidence: 51%
“…The inverse square-root dependence has been validated experimentally for many insulator materials to ''give a correct description of the decrease in dielectric strength of the surface with increasing insulator length.'' 15 When applied to thinner insulators, the relationship suggests that larger surface electric fields are required for surface flashover. For example, Pillai and Hackam 15 reported a flashover voltage of 40 kV for a 2-mm-thick quartz disk, corresponding to 0.2 MV/cm; using the aforementioned relationship, a flashover field of Ϸ9 MV/cm is predicted for a ͑quartz͒ surface length of 1 m under the same measurement conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely important to report the surface length, because of a well-known nonlinear dependence of the flashover voltage on surface length. The relationship, developed theoretically by Pillai and Hackam 15 for the prevailing mechanism of surface flashover ͑surface discharging in a layer of desorbed gas from the insulator surface͒, 8 predicts that the surface electric field required to cause flashover depends on the length of the insulator to a power law of Ϫ0.5. The inverse square-root dependence has been validated experimentally for many insulator materials to ''give a correct description of the decrease in dielectric strength of the surface with increasing insulator length.''…”
Section: Discussionmentioning
confidence: 99%
“…16 It was shown 17 that, assuming a cosine distribution of released electrons, the equilibrium in surface charge is reached when the angle between the electric field and the surface is equal to…”
Section: Secondary Electron Emission From Ferroelectricsmentioning
confidence: 99%
“…Recently, a method of deducing of the initial plasma parameters from temporal profiles of the density of expanding plasma has been developed. 8 It was shown that the initial plasma density in the stem of the discharge could reach (4 -40)ϫ10 16 cm Ϫ3 , and the initial electron temperature is 16 -20 eV. Such a high density corresponds to a pressure of neutral gas of 1-10 Torr at room temperature, assuming full ionization.…”
Section: Introductionmentioning
confidence: 99%